2023
DOI: 10.3390/biomedicines11030707
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota, LADA, and Type 1 Diabetes Mellitus: An Evolving Relationship

Abstract: There is much evidence confirming the crucial role played by the gut microbiota in modulating the immune system in the onset of autoimmune diseases. In this article, we focus on the relationship between alterations in the microbiome and the onset of diabetes mellitus type 1 and LADA, in light of the latest evidence. We will then look at both how the role of the gut microbiota appears to be increasingly crucial in the pathogenesis of these disorders and how this aspect may be instrumental in the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The gut microbiota is one of the most evolving fields of medicine in recent years [63], which is increasingly fascinating researchers worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is one of the most evolving fields of medicine in recent years [63], which is increasingly fascinating researchers worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on the microbiota in diabetes associated with developing acute peritonitis (Ortega et al, 2020;Craciun et al, 2022;Piccioni et al, 2023). Toniolo et al (2019) associated bacteremia and sepsis with this disorder of carbohydrate metabolism with Escherichia coli, Staphylococcus aureus, Streptococcus pneumoniae, Enterobacteriaceae, Enterococci, Pseudomonas aeruginosa, Candida albicans.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of smoking on the gastrointestinal system has been extensively examined as a potential risk factor for cancer, as noted by Cicchinelli et al (2023). Commencing with studies using animal models, researchers have observed that mice exposed to smoke exhibited dysbiosis in the gut microbiota, leading to an elevated occurrence of colorectal cancer.…”
Section: Health Implication Of Findingsmentioning
confidence: 99%